A survey of Ultrasound use in Prenatal Health Care in Iran - Sangestani, gita; khatiban, mhnaz (Advances in Nursing & Midwifery, 2012)
Abstract Background and Aim: These days, use of Ultrasound in Prenatal Health Care is debatable. So, this research has been performed to study use of Ultrasound in prenatal health care. Materials & Methods: This descriptive study was conducted in all mothers that were going to maternity hospital in Hamadan. Among them, 380 pregnant women were studied by the available Sampling based on all inclusion criteria. An information record sheet was filled for each patient through three methods: interview, studying the documents and observing the labor process according to the related case. Results: At least, Ultrasound has been done one time in 98.7% of pregnancies. The average rate of Ultrasound examination in pregnancies was 2.61%. Maximum request for Ultrasound examination was 8 times in 0.08% cases. There are three main reasons for Ultrasound examination: routine examination in prenatal health care (53.3%), to control or follow up pregnancy complication (33.14%) and mother’s request for knowing baby’s sex (13.56%). Because of different reasons, as, mother’s worries about unpleasant results of examination, 8% of all applied Ultrasound Examinations has not been performed. The final main finding demonstrated that 68.4% of pregnant women, who profit by prenatal healthcare including Ultrasound, were involved with a pregnancy complication such as Premature Rupture of Membrane (47.3%). Discussion &Conclusion: Regarding the results, that show, due to the increased use of Ultrasound technology in Prenatal Care in Iran and all around the world, it is necessary to design an appropriate method for applying Ultrasound to improve quality of Prenatal Health Cares. Keywords: Sonography-Prenatal ultrasound - Prenatal care